2011
DOI: 10.1021/ja200198v
|View full text |Cite
|
Sign up to set email alerts
|

An Organometallic Single-Ion Magnet

Abstract: An organometallic single-ion magnet is synthesized with only 19 non-hydrogen atoms featuring an erbium ion sandwiched by two different aromatic ligands. This molecule displays a butterfly-shaped hysteresis loop at 1.8 K up to even 5 K. Alternating-current (ac) susceptibility measurement reveals the existence of two thermally activated magnetic relaxation processes with the energy barriers as high as 197 and 323 K, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
395
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 754 publications
(432 citation statements)
references
References 19 publications
21
395
1
1
Order By: Relevance
“…This strategy has yielded a number of remarkable breakthroughs in the field [210][211][212][213][214][215][216][217][218]. In particular, the combination of metal centers possessing large spin-orbit coupling along with appropriate coordination environments can give rise to greater relaxation barriers than those observed for exchange-coupled clusters.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has yielded a number of remarkable breakthroughs in the field [210][211][212][213][214][215][216][217][218]. In particular, the combination of metal centers possessing large spin-orbit coupling along with appropriate coordination environments can give rise to greater relaxation barriers than those observed for exchange-coupled clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Multimetallic complexes of the lanthanide metals are of interest as molecular models for lanthanide-based polymers, 1,2 which have potential applications in magnetic materials, [3][4][5][6] molecular catalysis, 7,8 and luminescent devices. [9][10][11] The aromatic ligand pentalene [C 8 H 6 ] 2− (= Pn) has shown the ability to facilitate strong electronic delocalisation in anti-bimetallic transition metal compounds, 12 and promote coupling effects through the planar π-system of the bridging Pn ligand.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] The aromatic ligand pentalene [C 8 H 6 ] 2− (= Pn) has shown the ability to facilitate strong electronic delocalisation in anti-bimetallic transition metal compounds, 12 and promote coupling effects through the planar π-system of the bridging Pn ligand. [13][14][15][16] The development of the silylated pentalene ligand [1,4- 6 ] via solvent activation of THF (Scheme 1). 18 It was suggested that the strongly reducing nature of Sm(II) and the slightly larger size of this ion when compared to the smaller, less reducing Eu(II) and Yb(II), made it better stabilised, electronically and sterically, in the +3 oxidation state with Pn † .…”
Section: Introductionmentioning
confidence: 99%
“…The ligand field analysis with symmetry of C ∞v reveals an Ising-type ground state. However, the Ising nature of the molecule needs to be further confirmed by single crystal data due to the approximation [33]. Further, more flexible polydentate ligands could be applied for the polynuclear Lanthanide-based SMMs [34,35].…”
Section: Crystal Fieldmentioning
confidence: 99%